ON THE CLASSIFICATION OF ENVIRONMENTAL QUALITY STANDARDS IN THE REPUBLIC OF BELARUS - Tamara Vladimirovna, Рогожкина (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2022)
In the article the importance of normalization of environmental quality for the realization of the constitutional right of everyone to a healthy environment is considered. In order to develop a unified system of standards issues related to classification of standards are explored. Are offered to provide objective, spatial, temporal and subjectival domain of the standard. Objective domain of the standard concerns the determination of specific standardized environmental factors, is related to the choice of factors for the standardization. Spatial domain of the standard concerns the determination of the object, areas in which standards must be observed. Temporal domain of the standard is related to imparting to the standard timed or open-ended character. Subjectival domain of the standard concerns the determination of the subjects in the interest of which standard is established.